Health Risk Assessment of Petrol Filling Workers of West Bengal, India - Basak, Srijoni; Mandal Majee, Anindita (Universitas Airlangga, 2025)
Introduction: In recent decades, rapid urbanization has led to a surge in the number of automobiles on the roads, and consequently, an increase in petrol filling stations. In India, petrol stations are manually operated, and during fuel dispensing workers are routinely exposed to volatile organic compounds (VOCs) and vehicular exhaust. As a result, petrol filling workers face substantial health risks, though their well-being often receives minimal attention. This study aims to assess the adverse effects of VOC exposure on pulmonary function and evaluate associated health risks. Method: A cross-sectional study was conducted among 152 petrol filling workers and 100 control individuals. Spirometry and Peak Expiratory Flow rate tests were performed on both groups along with physical parameters. Respiratory symptoms were recorded via questionnaires. In addition, environmental analysis has been made for total VOCs, benzene, PM2.5 and PM10 and from this analysis carcinogenic and non-carcinogenic risk has been assessed. Results: Pulmonary function parameters were significantly lower in petrol filling workers than in controls. Odds ratios indicate increased risks of respiratory symptoms, including cough, phlegm, and chest tightness, correlated with years of exposure. Workers with over 20 years of exposure reported higher incidences of chronic cough (85%), chronic bronchitis (50%), and chest tightness (35%) compared to those with fewer years of exposure. Carcinogenic and non-carcinogenic risk assessments revealed elevated Lifetime Cancer Risk and Hazard Quotient values. Conclusion: Exposure to benzene, toluene, ethylbenzene, and xylene (BTEX) in petrol and diesel may reduce lung function and elevate the risk of respiratory impairment, alongside heightened carcinogenic and non-carcinogenic health risks.